2017
DOI: 10.3390/molecules22050726
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Copper Pollution on the Phenolic Compound Content, Color, and Antioxidant Activity of Wine

Abstract: The effects of copper pollution on the polyphenol content, color, and antioxidant activity of wine, as well as correlations among these factors, were investigated. Copper had clear influences on wine polyphenol content. At low copper concentrations, the concentrations of nearly all polyphenols increased, and the antioxidant activity values of the wine also increased. When the copper concentration reached the lowest level of the medium copper range (9.6~16 mg/L), most of the indices also improved. When the copp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 50 publications
1
17
0
Order By: Relevance
“…On fact, the copper content exceeding in the grape must happened from time to time, García-Esparza et al (2006) found that about 13% of grapes and 18% of wines exceeded the maximum copper residue in Otaly. On Nebbiolo, Australian and China, the phenomenon started to appear too (Marengo & Aceto, 2003;Sauvage et al, 2002;Sun et al, 2015bSun et al, , 2017Sun et al, , 2018. And in a short period of time, Bordeaux mixture pesticides are still difficult to be replaced (Li et al, 2008); this also means that the copper content in the vineyard as well as in the grape must will still continue to rise.…”
Section: Introductionmentioning
confidence: 99%
“…On fact, the copper content exceeding in the grape must happened from time to time, García-Esparza et al (2006) found that about 13% of grapes and 18% of wines exceeded the maximum copper residue in Otaly. On Nebbiolo, Australian and China, the phenomenon started to appear too (Marengo & Aceto, 2003;Sauvage et al, 2002;Sun et al, 2015bSun et al, , 2017Sun et al, , 2018. And in a short period of time, Bordeaux mixture pesticides are still difficult to be replaced (Li et al, 2008); this also means that the copper content in the vineyard as well as in the grape must will still continue to rise.…”
Section: Introductionmentioning
confidence: 99%
“…The TFO content was estimated using the slightly modified DMACA method (28) and the results were expressed as mg CTE/100 g FW. The TA content was estimated using the pH differential method (29) and the results were expressed as milligrams of cyanidin-3-glucoside (CGE)/100 g FW (mg CGE/100 g FW). All spectrophotometric measurements were performed on a UV-Vis double beam Hitachi U-3010 spectrometer (Hitachi, Kyoto, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Copper (Cu) is one of the heavy metals of great concern in the wine industry (Jia et al, 2015;Sun et al, 2017;Sun et al, 2018). It should be emphasized that Cu is an essential element for plants and, by definition, it is necessary for an organism to function properly, since it plays key roles in several biochemical and physiological processes connected to plant growth and development (Yruela, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Copper is an essential metal to nearly all organisms but has a very narrow optimum concentration range (Azenha et al, 2000;Ferreira et al, 2006;Sun et al, 2017). Above the physiological concentrations, copper can have inhibitory or even toxic effects on cell metabolism (Robinson and Winge, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation